Métodos de avaliação tridimensional do complexo craniofacial em tomografia cone beam - Weissheimer, André (2013)
Introduction : this thesis aimed to evaluate the software accuracy for 3D analysis of craniofacial complex in cone beam computed tomography (CBCT). With this purpose, two studies were performed. The first study evaluated the precision and accuracy of 6 imaging software programs for measuring the upper airway volume in CBCT. The second study aimed to validate a fast method for 3D superimposition of CBCT. Methods : in study 1, the sample consisted of 33 growing patients and 1 oropharynx acrylic phantom (OAP), scanned with iCAT scanner. The known OAP volume was used as gold standard (GS). Semi-automatic segmentations of the patients´ oropharynx (OP) and OAP was performed using Mimics, ITK-Snap, OsiriX, Dolphin3D, InVivo Dental and Ondemand3D software programs. In study 2, the sample consisted of CBCT scans of 18 patients. For 10 patients as a gold standard, the spatial position of the pretreatment CBCT volume was reoriented, saved as a reoriented volume, and then superimposed to the original image. For 8 patients, 4 non-growing and 4 growing patients, pre and post-treatment scans were superimposed. Superimposition accuracy was assessed by visual inspection and measured by using the CMF application and expressed via color maps. Results : in study 1, the OAP segmentations with Mimics, Dolphin3D, OsiriX and ITK-Snap showed less than 2% error in volume compared to the GS. Ondemand3D and InVivo Dental showed more than 5% error compared to the GS. In the OP segmentation, ITK-Snap, Mimics, OsiriX and Dolphin3D were statistically significantly different (P<.05) from InVivo Dental. No statistical difference (P>.05) was found between InVivo Dental and OnDemand3D. In study 2, Superimposition error of the spatial reorientation as measured by the color-coded surface distances was less than 0.5mm. Superimposition error of pre and post treatment scans for both growing and non-growing patients at the cranial base were smaller than 0.5 mm, which was considered acceptable and clinically insignificant. Conclusion : in study 1, all 6 imaging software programs were reliable but showed errors in the volume segmentation of OP. Mimics, Dolphin3D, ITK-Snap and OsiriX were similar and more accurate than InVivo Dental and Ondemand3D. In study 2, the voxel-based superimposition method evaluated was reproducible in different clinical conditions, time-efficient and potentially applicable for both research and clinical practice.